2009
DOI: 10.1016/j.jcis.2009.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol effects on the formation and rheology of hexagonal phase and related gel emulsion

Abstract: We have investigated the effects of glycerol on the formation and rheology of hexagonal phase (H(1)) and related O/H(1) gel emulsion in the water/C(12)EO(8)/dodecane system at 25 degrees C. It has been found that the aqueous solution of C(12)EO(8) forms H(1) phase, which could solubilize some amounts of dodecane. Beyond the solubilization limit, oil is separated and a two-phase region or H(1)+O phase appeared. Due to high viscosity of the H(1) phase, allows forming O/H(1) gel emulsion at the H(1)+O region. Rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
2
14
1
1
Order By: Relevance
“…It is clearly shown that the values of |h*| steeply increase in the single I 1 phase with the squalane content and reach the highest value at the boundary point (~10 7 Pa s). This value is slightly lower than the reported value in other systems 15,24) . The value of G′ also increases in the I 1 phase and decreases in the I 1 +O or O/I 1 gel emulsion.…”
contrasting
confidence: 71%
“…It is clearly shown that the values of |h*| steeply increase in the single I 1 phase with the squalane content and reach the highest value at the boundary point (~10 7 Pa s). This value is slightly lower than the reported value in other systems 15,24) . The value of G′ also increases in the I 1 phase and decreases in the I 1 +O or O/I 1 gel emulsion.…”
contrasting
confidence: 71%
“…7 b. Similar results have been reported for the O/I 1 emulsion formed in the water/C 12 EO 8 / dodecane system with glycerol 8 .…”
Section: Figsupporting
confidence: 86%
“…Emulsions which exhibits G' values higher than G'' (Figure 14) are described as more stable than formulations with G'' values higher than G' (Figure 15), since they tends to recovery its initial structure faster and more efficiently than the others, and are less susceptible to the gravitational forces which retards or avoids the coalescence process and the phase separation of emulsions (Alam and Aramaki, 2009). So, the G' values higher than G'' in emulsions is a desirable feature, being an indicative of stability of the cosmetic system.…”
Section: Rheologymentioning
confidence: 99%